Examining the Impact of the Employee Motivation to the Organizational Commitment in General Insurance Corporations in Ho Chi Minh City, Vietnam - Hieu, Vu Minh; Cham, Pham Thi (International Journal of Psychosocial Rehabilitation, 2020)
Employee motivation and organizational commitment become an area of emergent concern in the literature and in the real world. This study is to explore the impact of employee motivation on the organizational commitment done in general insurance corporations in Ho Chi Minh City, Vietnam. The authors used secondary and primary data to elicit information from respondents. Secondary data has been collected from different sources in the works of literature and in the published magazine. The primary data is from the 250 respondents through surveyed questionnaires and three in-depth interviews with staff and head of department in the general insurance corporations in Ho Chi Minh City, Vietnam. The results show that employee motivation impacts organizational commitment. Furthermore, after the findings, the recommendations and implications to the business owners and managers have been established. The limitation and further study are also presented.